2012
DOI: 10.1080/10640266.2012.668476
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Job Burnout in Eating Disorder Treatment Providers

Abstract: Although job burnout is common in mental health care settings, almost no research has examined burnout in eating disorder treatment providers. Using qualitative methodology, this study examined a) perceived contributors of burnout, b) efforts to manage burnout, and c) recommendations for avoiding burnout in a sample of professional eating disorder treatment providers. Recruited via professional organizations, 298 participants completed an online questionnaire designed by the authors. Qualitative responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 48 publications
1
41
0
2
Order By: Relevance
“…In 29 studies, participants reported that their work with individuals with EDs was “emotionally draining” (treatment provider; Warren et al, , p. 183) in the context of high levels of resistance and relapse, the shock of emaciation, feeling manipulated by service users, and difficulties with other professionals and families. Many clinicians described experiencing frustration, and some reported anger, in response to service users' rejection of treatment, denial, and relapse: “I looked after a girl who used to rip out the naso gastric feeding] tube….After some time, you would get feelings of immense anger and frustration” (health professional; Walker & Lloyd, , p. 142).…”
Section: Resultsmentioning
confidence: 99%
“…In 29 studies, participants reported that their work with individuals with EDs was “emotionally draining” (treatment provider; Warren et al, , p. 183) in the context of high levels of resistance and relapse, the shock of emaciation, feeling manipulated by service users, and difficulties with other professionals and families. Many clinicians described experiencing frustration, and some reported anger, in response to service users' rejection of treatment, denial, and relapse: “I looked after a girl who used to rip out the naso gastric feeding] tube….After some time, you would get feelings of immense anger and frustration” (health professional; Walker & Lloyd, , p. 142).…”
Section: Resultsmentioning
confidence: 99%
“…There have been growing calls to address these stressors through professional support and development mechanisms [4-7]. Clinical supervision, in particular, is regarded as a key method for helping to avoid burnout and maintain professional wellbeing [7,8] as well as for holding mental health professionals accountable [8-10]. Clinical supervision refers to a principled and contractual relationship, in which the supervisor assists the supervisee to reflect on their clinical work with patients/clients [11].…”
Section: Introductionmentioning
confidence: 99%
“…As an indication of the scope of these occupational studies, in 2012 alone, burnout research was done on teachers (Pishghadam and Sahebjam, 2012), doctors (Siu et al, 2012), nurses (van der Doef et al, 2012), clergy (Barnard and Curry, 2012), occupational therapists (Gupta et al, 2012), music therapists (Kim, 2012), fl ight attendants (Chen and Kao, 2012), correctional staff (Lambert et al, 2012), professional caregivers in longterm care settings for the elderly (de Rooij et al, 2012), working undergraduate university business students (Galbraith and Merrill, 2012), dental and medical students (Prinz et al, 2012), eating disorder treatment providers (Warren et al, 2012), and employees at a large public hospital (Hämmig et al, 2012), to name but a few.…”
Section: Introductionmentioning
confidence: 99%